2018
DOI: 10.1155/2018/8529104
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Gammadelta T Cells from Cord Blood: A Therapeutical Possibility

Abstract: Gammadelta (γδ) T cells are found in both blood and tissues and have antiviral and antitumor properties. The frequency of γδ T cells in umbilical cord blood (UCB) is low, and the majority express δ1, in contrast to blood, whereas the main subset is δ2γ9 T cells. UCB γδ T cells are functionally immature, which together with their scarcity complicates the development of UCB γδ T cell therapies. We aimed to develop an effective expansion protocol for UCB γδ T cells based on zoledronate and IL-2. We found that cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Because the majority of gd T-cell clinical trials used fresh cells, information regarding cryopreservation of gd cells for clinical trials is limited. A research study found that gd T cells expanded from umbilical cord blood (UCB) and cryopreserved in the complete medium with 10% DMSO maintained tumor-killing capacity showing a potential for clinical application [38].…”
Section: Car T-cell Therapymentioning
confidence: 99%
“…Because the majority of gd T-cell clinical trials used fresh cells, information regarding cryopreservation of gd cells for clinical trials is limited. A research study found that gd T cells expanded from umbilical cord blood (UCB) and cryopreserved in the complete medium with 10% DMSO maintained tumor-killing capacity showing a potential for clinical application [38].…”
Section: Car T-cell Therapymentioning
confidence: 99%
“…While extensive research has convincingly established the key contribution of costimulation on αβ T cell functions, the functional relevance of co-stimulatory/co-inhibitory molecules on γδ T cells in the context of suppressive activity as well as a role for CD28 in the acquisition of a suppressive phenotype of Vδ2 + γδ T cells remains to be defined. CD28 is expressed by 40-60% of freshly isolated human peripheral γδ T cells, but downregulated after TCR signaling so that very few (< 10%) activated γδ T cells express CD28 [63][64][65]. CTLA-4 is expressed only marginally before and after PAgstimulation on the cell surface [63].…”
Section: Discussionmentioning
confidence: 99%
“…CD28 is expressed by 40-60% of freshly isolated human peripheral γδ T cells, but downregulated after TCR signaling so that very few (< 10%) activated γδ T cells express CD28 [63][64][65]. CTLA-4 is expressed only marginally before and after PAgstimulation on the cell surface [63]. Our data confirm the downregulation of CD28 in Vδ2 + T cells after TCR signaling, i.e., in this study after IPP/IL-15-stimulation, and also the only marginal expression of CTLA-4 before and after IPP/IL-15-stimulation (Supplementary Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a single CB unit administration was confirmed in children under 10 [97]. A technique of the ex vivo expansion of CB-derived stem cells has been developed, and its clinical efficacy has been positively verified, despite initial problems [114][115][116][117][118]. However, the cells expanded ex vivo undergo changes in genetic expression, which is an issue that requires further studies [119].…”
Section: Past and Future Perspectivesmentioning
confidence: 99%